ANALISIS RISIKO PENDAPATAN PADA USAHATANI PADI ORGANIK DI DESA LOMBOK KULON KECAMATAN WONOSARI KABUPATEN BONDOWOSO - Ma'ruf Asbullah; Triana Dewi Hapsari; Sudarko Sudarko (University of Jember, 2017)
Organic farming has become one of risky farming systems, because its yield could be lower than anorganic farming. Moreover, low yield can lead to a suffer in financial loss on organic farming. This might be caused by the changing in input usage when farmers changed their farming system from anorganic to organic farming. The research was aimed to determine : 1) income’s risk of organic farming by different cropping seasons. 2)income’s risk of organic farming based on its harvested area. The research was designed as descriptive and analytical research. The sampling farmers were selected by using proportioned stratified random sampling, Structural interview and documentational techniques were employed to gain informations about income’s risk in organic farming. Coefficient Variances was employed as primary analytical tool in this research. The result showed that : (1) risk in organic farming can be higher as long as it was applied by farmers. This result was concluded based on Coefficient Variance in farmer’s group both in Mandiri I which has 45,54% and Mandiri IB which has 41,34%. (2) according to Coeffient Variance Analysis, risk in organic farming can be lower if farmers have few harversted area. The Coeffient Variance for each categories in harvested area were : narrow harvested area (47,53%); medium harvested area (34,61%) and large harvested area (24,45%). Keywords: Organic Rice, Income, Risk